Hydrodynamic and kinetic processes of the mineral fertilizer granules encapsulating in the multistage device with suspended layer - Yukhymenko, Mykola; Ostroga, Ruslan; Artyukhov, Artem (Eastern-European Journal of Enterprise Technologies, 2016)
One explained the possibility of reducing economic and environmental indicators in the production of mineral fertilizers by covering their surface with the protective coating (capsule), which creates additional resistance to mass transfer in the process of fertilizer dissolving. It is proved that the use of organic suspensions as a material for the capsule shell is very promising. Using a many-stage countercurrent contact of a fluidizing agent and dispersed phase in the fluidized bed during the heat exchange process is a perspective way of reducing economic and energy costs. Therefore, in order to reduce the cost of processing wet materials and increase the uniformity of particle size distribution of the final product one offered to carry out the process of granules coating with organic substance in a many-stage shelf apparatus with the suspended layer. One defined structural features of the shelf device classification section and experimentally established influence of the shelf length and degree of its perforation on the process of the fine fraction entrainment. Fine fraction entrainment is reducing with the increase of the shelf length. Also, pneumatic classification process of the material for the shelves with open area up to 5 % is more intense than for the shelves with open area of more than 15 %. The kinetics of mineral granules enlargement during their encapsulation with organic suspension is experimentally and theoretically studied. It was found out that in the process of encapsulation the curve of particle size distribution has one typical maximum. It confirms the theory of uniform enlargement of granule surface, when organic substance is fixed on the particle surface in the form of a solid layer and no shearing of the granule coating takes place. It enables to obtain the complete organic shell (capsule) on the mineral granules surface. One studied the transfer of material flows in the individual stages of the apparatus granulation section. A mathematical model of the granulation kinetics in the many-stage shelf apparatus, which takes into account changes of granules distribution density as to their sizes in each contact stage is developed. The resulting model is characterized by a cell structure in which the material flow is seen as divided into a number of series-connected zones, wherein different granulation modes are implemented.